HEPATOPROTECTIVE EFFECT AND GC-MS ANALYSIS OF TRADITIONALLY USED BOSWELLIA SACRA OLEO GUM RESIN (FRANKINCENSE) EXTRACT IN RATS - Asad, Mohammed; Alhumoud, Meshal (African Journal of Traditional, Complementary and Alternative Medicines, 2015)
Background: The water extract of oleo-gum-resin of Boswellia sacra Fleuckiger (Burseraceae) is used in the treatment of liver problems in theMiddle East and Arab-African countries. The present study was carried out to evaluate its effect on liver injury induced by carbon tetrachloride inacute and chronic liver injury models.Materials and Methods: The Boswellia sacra extract was administered at doses of 2 ml/kg and 5 ml/kg. Silymarin, a known hepato-protectiveagent was used as standard. The extract was subjected to GC-MS analysis to determine the presence of various phyto-constituents.Results: The Boswellia sacra extract at tested doses of 2 ml/kg and 5 ml/kg significantly reduced the elevated serum levels of biomarkers in liverdamage. The hepatoprotective effect was supported by changes in histopathology. The GC-MS analysis of the extract revealed the presence ofseveral phyto-constituents that included menthol, 3-cyclohexen-1-ol and octanoic acid.Conclusion: The water extract oleo-gum-resin of Boswellia sacra possesses hepatoprotective activity, as claimed by traditional healers within theMiddle East and Arab-African countries.